Perceived Institutional Barriers Among Clinical and Research Professionals: Minority Participation in Oncology Clinical Trials. Issue 5 (May 2021) - Niranjan, Soumya J.; Wenzel, Jennifer A.; Martin, Michelle Y.; Fouad, Mona N.; Vickers, Selwyn M.; Konety, Badrinath R.; Durant, Raegan W.
Abstract : PURPOSE: In general, participation rates in cancer clinical trials are very low. However, participation rates are especially low among the socially disadvantaged and racial and ethnic minority groups. These groups have been historically under-represented in cancer clinical trials. Although many patient-related barriers have been studied, institutional factors that are essential for building clinical research infrastructure around the clinical trial enterprise in academic medical centers have been underexplored. MATERIALS AND METHODS: We assessed perspectives of cancer center professional stakeholders on the institutional factors that can potentially influence racial and ethnic minority recruitment for cancer clinical trials. Ninety-one qualitative interviews were conducted at five US cancer centers among four stakeholder groups: cancer center leaders, principal investigators, referring clinicians, and research staff. Qualitative analyses examined response data focused on institutional factors related to minority recruitment for cancer clinical trials. RESULTS: Four prominent themes emerged regarding institutional barriers among clinical and research professionals. (1) There are no existing programs currently being used to recruit or retain minorities to clinical trials. (2) Institutional efforts are needed to increase trial participation and are not specific to potential minority participants. (3) Access to cancer clinical trials and navigation within an Academic Medical Center need to be simplified to better facilitate recruitment of minority patients. (4) Community outreach by cancer centers will increase clinical research awareness in the community. CONCLUSION: Our research highlights the need to address institutional barriers to improve the success of minority recruitment. To increase participation among minority populations, medical centers must address mutable institutional barriers such as setting specific minority recruitment goals for cancer clinical trials, ensuring that cancer clinical trials are accessible, especially to minority patients, and supporting sustained community outreach programs to increase clinical research awareness.